2018
DOI: 10.4103/jios.jios_72_17
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for Accelerating Orthodontic Tooth Movement: A Systematic Review

Abstract: injections of prostaglandins, 1,25(OH)2 D3 (the active form of Vitamin D3), osteocalcin, and relaxin around the alveolar socket, but they have the undesirable side effects of local pain and discomfort during the injections. [4] Surgical category includes alveolar decortication, corticotomy, distraction of the periodontal ligament, and distraction of the dentoalveolus. The idea of surgically accelerated tooth movement although more than a century old has only gained momentum and interest during the past 10 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Various methods have been described in the literature for speeding up space closure. 11,26 However, only recently have attempts been made to combine the two methods and check for any synergistic effect the 27 The authors concluded that the combination was more effective than the application of each technique separately. A similar synergistic effect may be observed if MOPs are combined with any other technique.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various methods have been described in the literature for speeding up space closure. 11,26 However, only recently have attempts been made to combine the two methods and check for any synergistic effect the 27 The authors concluded that the combination was more effective than the application of each technique separately. A similar synergistic effect may be observed if MOPs are combined with any other technique.…”
Section: Discussionmentioning
confidence: 99%
“…These brackets were considered passive self-ligating appliances despite the use of nickel titanium springs as the archwire was passively held in the bracket slot. 11 Finite element analysis revealed that there was no clip stress after the insertion of 0.019 3 0.025-inch stainless steel wire, making the Smart Clip bracket effectively a passive self-ligating bracket. 17 The control consisted of patients treated with 3M Gemini brackets supplemented with MOP.…”
Section: Interventionsmentioning
confidence: 98%
See 1 more Smart Citation
“…(Hatrom et al, 2020) Piezocision demonstrated a mean improvement of 43% and required substantially less time overall than the control group. (Shirude et al, 2018) However, piezocision studies have yielded contradictory. (Hatrom et al, 2020) This is because some studies showed that corticotomy and piezocision did not show root resorption, whereas other studies showed that periodontal disorders caused root resorption in one of the six.…”
Section: Reviewmentioning
confidence: 99%